International Trade and Its Impact on Economic Growth in Mexico In Relation To the Mexico-Colombia Free Trade Agreement. Agricultural Sector 2016-2018 - ÁVALOS, María del Sol Zetina; LÓPEZ RODRÍGUEZ, William Baldemar; TECİLLO, Francisco Javier Jiménez (PEARSON JOURNAL, 2023)
International trade has allowed countries to have a greater relationship around the export and import of goods and services, it has been a fundamental part of international economic growth allowing countries to extend their borders thanks to the conclusion of international treaties, which have the function of achieving that between two or more countries can export and import goods and services among themselves, avoiding double taxation in addition to obtaining various benefits which were agreed by the delegations assigned by each of the countries involved. Mexico currently has international agreements with 14 countries, which has allowed it to expand its market. One of them is the Mexico-Colombia Free Trade Agreement, which entered into force in January 1995, which would see its closure in 2006 with the departure of Venezuela, but which resulted in negotiations between Mexico and Colombia to close the bilateral treaty that is in force until today. Since then, Colombia has become Mexico’s second largest trading partner in Latin America. Exports of Mexican products have had a great growth, being reflected mainly in the agricultural sector, where agri-food exports due to the variety, health, safety and quality of the products Mexicans have contributed to the country having a larger trade surplus.